Potential contribution to the invasion process of different reproductive strategies of two invasive roses - Mazzolari, Ana Clara (2017)
The type of reproductive system may be an important trait for the establishment and maintenance of populations of invasive plant species in new areas, as it can influence their demography and genetics. We studied the breeding system of two exotic invasive species, Rosa rubiginosa and R. canina, in a natural reserve in Argentina, using a combination of pollination experiments. We asked how the different reproductive modes of these species affect the quantity and quality of the fruits and seed produced. Our results show that both invasive rose species have an array of reproductive strategies, and that they are able to invade without pollinators, as they can produce seeds in the same quantity and quality through wind-pollination, self-pollination, and apomixis. Such lack of dependence on pollinators and pollination for reproduction should enhance colonization into new areas, suggesting the need of intensive monitoring of spread and dispersal. Considering that both species are successful invaders in the region, our results are in line with Baker's rule, which posits that plants capable of uniparental reproduction are more likely to invade new areas.